Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1743-6109.2008.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Sexual Attitudes of Students in Health Professions

Abstract: Introduction Patients' sexual concerns are frequently underestimated because of health professionals' reluctance to address sexual health issues. Though it has been documented that sexual attitudes are extremely influential in everyday clinical practice, limited data exist on identifying health professionals' attitudes. Aim To explore sexual attitudes in medical students and students in allied health professions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 33 publications
5
30
4
3
Order By: Relevance
“…Earlier research has shown that patients with chronic conditions often rate their sexual health as important, but neglected by health care professionals (Bitzer, Platano, Tschudin, & Alder, 2007;Papaharitou et al, 2008), despite research showing that health care providers can moderate the sexual expression of persons suffering from chronic disease (O'Dea, Shuttleworth, & Wedgwood, 2012), and the patients have a right to have eventual sexual problems thoughtfully identified and addressed (Krebs, 2007). Maintaining professional boundaries is essential when working with sexual health, and students in health care professions need to have sufficient knowledge of how to work with sexual health and to feel confident that they are still upholding professional boundaries, despite the sensitive subject and the hands-on practice that nursing and rehabilitation often include (Soundy, Stubbs, Jenkins, & Cooper, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier research has shown that patients with chronic conditions often rate their sexual health as important, but neglected by health care professionals (Bitzer, Platano, Tschudin, & Alder, 2007;Papaharitou et al, 2008), despite research showing that health care providers can moderate the sexual expression of persons suffering from chronic disease (O'Dea, Shuttleworth, & Wedgwood, 2012), and the patients have a right to have eventual sexual problems thoughtfully identified and addressed (Krebs, 2007). Maintaining professional boundaries is essential when working with sexual health, and students in health care professions need to have sufficient knowledge of how to work with sexual health and to feel confident that they are still upholding professional boundaries, despite the sensitive subject and the hands-on practice that nursing and rehabilitation often include (Soundy, Stubbs, Jenkins, & Cooper, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gender, patient's age, personal values, and experiences influence students' attitudes toward sexual issues, and negative attitudes can impede effective sexual health consultations (Areskoug-Josefsson & Gard, 2015;Krebs, 2007). Awareness has to be raised of the students' own values and prejudices and knowledge of their attitudes towards working with sexual health, in order to address those issues with increased knowledge and competence (Krebs, 2007;Papaharitou et al, 2008;Sung, Huang, & Lin, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areskoug-Josefsson & Oberg, 2009;Egan et al, 2013;Josefsson & Gard, 2012;Rosenbaum, 2006). To provide sufficient sexual health rehabilitation, health care professionals need not only to recognize the biomedical view of sexual health, which is common among health professionals, but also to incorporate in their caring practice the biopsychosocial model of sexual health (Papaharitou et al, 2008;Penwell-Waines et al, 2014). In this study the definition of sexual health by the World Health Organization will be used (World Health Organization, 2006 In the study by Haboubi and Lincoln, health professionals agreed that sexual health could be part of care and rehabilitation for patients, but there was a need for more knowledge and education concerning sexual health and communication about sexual health issues (Coleman et al, 2013;Haboubi & Lincoln, 2003).…”
mentioning
confidence: 99%
“…Obecnie jedno z podstawowych źródeł informacji z zakresu seksualności stanowią mass media, a przede wszystkim Internet [12][13][14][15][16][17][18][19]. Ten ostatni jako forma samokształcenia oprócz zapewnienia anonimowości posiada wiele innych zalet, takich jak niskie koszty czy brak dyskryminacji, a co więcej, najczęściej nie wymaga mobilności i jest łatwo dostępny [20].…”
Section: Dyskusjaunclassified